THE ANTIOXIDATIVE DEFENCE IN WOMEN WITH EXTERNAL ENDOMETRIOSIS - L. V. Adamyan; O. N. Loginova; M. M. Sonova; K. N. Arslanyan (Акушерство, гинекология и репродукция, 2016)
We studied the indexes of antioxidative defence – the concentration of active form of enzymes ceruloplasmin (CP) and transferin (TF) and NO-capacity of the protein of blood in 60 women with external endometriosis by method spectroscopy. The concentration of active form of ceruloplasmin was increased and the concentration of transferin was decreased in women with external endometriosis; the index CP/TF was increased. The NO-connective capacity of theblood was significant increased in this group of women comparing with their relatives and the control (healthy women) group. These changes are the result of the breach of balance in the system oxidant\antioxidant and the development of oxidative stress in this group of women.